Holocene environments of the southeastern Pampas, Argentina: Multi-proxy evidence from an alluvial sequence at arroyo Claromecó - Prieto, Aldo R. (2010)
We summarize the results of a multi-proxy study from a 14C-dated alluvial outcrop sequence at arroyo Claromecó (38°50'S; 60°0'W). The results are based on gastropod and palynomorph analyses, alluvial history and both δ18O and δ13C isotopic values. Gastropods density and abundance were calculated and shell fragmentation was evaluated for taphonomic analysis. Between 7200 and 6540 years before present (BP), sedges associated with halophytic vegetation and the coexistence of Succinea meridionalis d'Orbigny and Heleobia parchappii d'Orbigny suggest the development of extensive, shallow, freshwater-brackish wetlands. These environmental conditions are in agreement with slight δ13C and δ18O values suggesting humid conditions. Between 6540 and 6000 years BP the presence of Heleobia australis d'Orbigny, high variability of δ13C and a δ18O positive trend are related to the influence of marinebrackish water associated with the Holocene sea-level highstand. During this period, halophytic vegetation was developed. At 6000 years BP a greater expansion of wetlands occurred that persisted until 3440 years BP. H. australis disappeared and the dominance of H. parchappii with good preservation suggest low energy conditions. The highest fluctuations in the isotopic values and palynological spectra suggest an unstable environment related to desiccation/ evaporation events, sea-level fall and fresh water input related to precipitation. Between 3440 and 2500 years BP a channel incision occurred possibly triggered by sea-level fall. After 2500 years BP, the palynological spectra from sediments sporadically deposited in relation to fluvial overflow are in agreement with the high proportion of poorly preserved H. parchappii and Mytilidae remains that indicate a reworked assemblage. Slighter and variable δ13C and δ18O trends and the halophytic and psammophytic vegetation reflect the wetland desiccation under dry conditions. After 1000 years BP, psammophytic communities developed reflecting sand dunes. Multi-proxy evidences provided an integrated reconstruction of Holocene vegetation and paleoenvironmental conditions related to fluvial activity, sea-level changes and climatic variability.